Peripheral Nerve Disorders P-PN001. Electromyography (EMG) of abductor pollicis brevis (ABP) muscles in diabetes mellitus type 2. Issue 8 (August 2021) - Maya Limbu, Dil; Poudel, B.H.; Thakur, Dilip; Maskey, Robin
Abstract : Introduction . The prevalence of chronic disease diabetes mellitus is rapidly rising all over the globe. The number of diabetic mellitus patients with diabetic neuropathy is increasing as estimated as 45% of patients develop diabetic polyneuropathy. Methods . The study was done in 10 (M = 4, F = 6, age 51.38 ± 11.71 years) consenting diabetic patients. sEMG of ABP muscles were recorded during rest and contraction state. Values obtained were compared between male and female diabetic groups. An independent t-test was applied to analyze the data. Results . EMG amplitude of right and left ABP muscles at rest are (8.67 ± 1.15, p < 0.002 vs 5.00 ± 0.00, 10.00 ± 0.00, p < 0.001) were decreased significantly in male than in female. Only EMG amplitude of left ABP muscles at contraction (243.60 ± 51.48 vs 124.00 ± 117.78, p < 0.042) was decreased significantly in male than in female diabetic group. EMG frequency of right and left ABP muscles (53.45 ± 72.92, 76.81 ± 11.42, p < 0.001) at contraction was decreased significantly in male than female diabetic group. Conclusion . The results suggest neuropathy can be detected early by the EMG test. Gender affects EMG parameters in diabetic patients.